Performance of sown species and weed ingress in new dairy pastures based on tall fescue and perennial ryegrass - Tozer, K.N.; Minnee, E.M.K.; Cameron, C.A. (New Zealand Plant Protection, 2014)
Poor performance of perennial ryegrass (Lolium perenne) and subsequent weed ingress reduces pasture productivity Tall fescue (Schedonorus arundinaceus) is more droughttolerant than perennial ryegrass and may perform better in summer dry upper North Island environments thus reducing weed ingress To compare swards based on perennial ryegrass and tall fescue for performance of sown species and weed ingress a replicated grazed plot study was established Measurements were made every 3 months from May 2010 until May 2013 Percentage cover of sown species at the canopy surface was significantly higher in perennial ryegrass than tall fescue swards over 3 years By the end of the third year basal and canopy cover of unsown species in tall fescue swards reached 28 and 40 respectively compared with only 13 and 7 respectively in perennial ryegrass Perennial ryegrass swards performed better and may provide a better option for keeping out weeds within the first 3 years of sowing